Analysis of the gut microbiome in obese native Tibetan children living at different altitudes: A case–control study - Du, Wenqi; Liu, Linxun; Ma, Yan; Zhu, Qinfang; Jia, Ruhan; Han, Ying; Wu, Ziyi; Yan, Xin; Ailizire, Ainiwaer; Zhang, Wei (Frontiers in Public Health, 2022)
In this paper, 16S rRNA gene sequencing and blood lipid metabolism indices were used to study the characteristics of the intestinal flora present in faeces and the changes in blood lipid metabolism in obese children from Tibet who reside at different altitudes and to study the correlation between blood lipid metabolism indicators and intestinal flora. The results showed the following. (1) The triglyceride (TG) and low-density lipoprotein (LDL) levels in the obesity groups were higher than those in the normal-weight groups, and those in the high-altitude obesity groups were lower than those in the plain obesity groups. (2) 16S rRNA gene sequencing results showed that altitude affects the composition and relative abundance of the gut microbiota. These parameters were basically the same in the low-altitude groups, while they were significantly lower in the high-altitude groups than in the low-altitude groups. (3) Groups who live at different altitudes and have different body weights are characterized differences in dominant bacterial genera. Megamonas was closely related to obesity, and its relative abundance in the low-altitude groups was higher than that in the high-altitude groups. Prevotella was associated with altitude, and its relative abundance in the high-altitude groups was higher than that in the low-altitude groups. In addition, Prevotella inhibited changes in the abundance of Escherichia-Shigella. The lower prevalence of obesity and the incidence of intestinal inflammation at high altitudes are related to the abundance of Prevotella. (4) There was a correlation between the gut microbiota and lipid metabolism indicators. The abundance of Romboutsia was positively correlated with the TG and LDL levels but negatively correlated with the HDL levels, the abundance of Akkermansia was negatively correlated with the LDL levels, and the abundance of Blautia was negatively correlated with BMI and the LDL levels. Conclusions: the diversity of intestinal flora was varied by body weight and altitude, with lower diversity in higher altitude and lower body weight. Prevotella plays a key role in suppressing obesity at high altitudes.